The corrosion behavior and passive film structure of industrial pure titanium with different Fe content in hydrochloric acid - Xingyu Ou-yang; Yang Yu; Wenjun Ye; Wenjing Zhang; Qiang Liu; Songxiao Hui (Journal of Materials Research and Technology)
In this paper, the corrosion behavior and passive film structure of three Ti-xFe (x = 0.2, 0.5, 1.0 wt%) materials in 1 M hydrochloric acid were studied. The results revealed that the microstructures of Ti-xFe hot rolled plates were large lamellars α-Ti and fine lamellars β-Ti, and Fe was mainly enriched in β-Ti. Immersion experiment showed that the corrosion rate increased as Fe content increased and β-Ti corroded preferentially. Electrochemistry tests result showed that the corrosion current density increased and the polarization resistance decreased with Fe addition, and all materials formed a dense and uniform passive film. TEM and XPS results proved that the passive film was a double-layer structure, the outer layer is dense TiO2 and the inner layer content Ti2O3 and TiO. And the addition of Fe will reduce the content of TiO2 in the outer layer while Fe did not appear in the passive film. The results of AFM showed that β-Ti had lower volte potential, which caused the micro galvanic cells formed by β-Ti and α-Ti.